Penerapan Model Pembelajaran Student Teams Achievement Divisions dalam Pengembangan Pola Dasar Lengan : Application of the Student Teams Achievement Divisions Learning Model in the Development of Basic Arm Patterns - Mutiara Suci Siregar; Hilman Haidir (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
The development of basic sleeve patterns is an important part of the basic skills of the Fashion Design subject, especially in making clothes that fit the size and shape of the body. However, in practice, most students still consider this material difficult because it requires a good understanding of measurement techniques, calculations, and pattern construction. This study aimed to examine the effectiveness of implementing the Student Teams Achievement Divisions (STAD) cooperative learning model as a strategic effort to improve students' understanding of the material on the development of basic sleeve patterns. This study used a Classroom Action Research (CAR) approach, implemented in two cycles. The subjects were 21 grade X Fashion Design students at SMKS Setia Budi Binjai. Data collection techniques included observation, interviews, questionnaires, tests, and documentation in the form of photos of student activities and work results. The results showed that applying the STAD model can improve student learning outcomes. The percentage of student learning completion increased from 76.19% in cycle I to 85.71% in cycle II. In addition to the increase in grades, this study also noted improvements in student activity, collaboration between students, and responsibility in completing group assignments. Based on these findings, the STAD learning model effectively improves students' understanding of the material on developing basic arm patterns and forming positive attitudes in learning.